Analisis Kelayakan Finansial Internal Rate of Return (IRR) dan Benefit Cost Ratio (BCR) pada Alternatif Besaran Teknis Bangunan Pasar Cinde Palembang - Ika Sulianti; Lina Flaviana Tilik (PILAR, 2013)
This paper discusses the feasibility analysis of financial internal rate of return (IRR) and benefit cost ratio (BCR) on Cinde market which is one of the oldest markets in Palembang. Feasibility analysis  is done by creating two design alternatives which  were different  from existing alternative and assumes revenues received later. By creating different alternatives, land area, kiosks and parking lot,  alternative A has a 26,08% IRR and BCR 1.18. This alternative makes buyers much easier to go directly to the floor or parking lot they want to go to. Effect of technical quantities of market building will greatly affect the financial feasibility with reference to the existing standard.